Possible Impact of Boreal Winter Siberian High on ENSO Development in the Following Year - Fu, Jiayu; Liu, Minghong; Wang, Run; Wang, Yuwen; Zhao, Shuo (Frontiers in Earth Science, 2022)
Siberian High (SH) is the dominant pressure system located in the mid-high latitudes of Eurasia during boreal wintertime. This study reveals a triggering impact of SH variation in preceding winter on the following ENSO events, and gives a possible explanation via diagnosing the SH-associated air-sea response over the tropical Pacific and North Pacific. When SH is anomalously enhanced (suppressed) during boreal winter, an Aleutian Low enhanced (suppressed) response will occur over the downstream North Pacific. The Aleutian Low response gradually evolves into a meridional dipole structure similar to the negative (positive) phase of the North Pacific Oscillation (NPO) during the following spring and early summer. Correspondingly, the oceanic response in the North Pacific features a pattern similar to the negative (positive) phase of the Victoria mode. These SH-associated air-sea responses over the subtropical North Pacific will be maintained and further delivered into the tropical Pacific through the so-called seasonal footprinting mechanism, which favors the Bjerknes feedback established around boreal summer and finally grows into a La Niña (El Niño).